2006
DOI: 10.2151/sola.2006-027
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Intense Tropical Cyclone Days in the Western North Pacific

Abstract: Variability in tropical cyclone (TC) days in the western North Pacific (WNP) since the late 1970s is investigated based on two datasets. As an overall behavior, the intense TC days have increased for the last 30 years from both the Japan Meteorological Agency (JMA) dataset and the Joint Typhoon Warning Center (JTWC) dataset. Both datasets show that TC days with an intensity of Saffir-Simpson category 2 or higher have increased by 15 30% over the past 30 years. In terms of the detailed behavior of this increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 16 publications
1
73
0
Order By: Relevance
“…The result is the same if the analysis is extended to include 2005.This downward trend is statistically significant at the 5% level (all significant tests are based on t tests).The trend signifies a falling tendency in typhoon intensity in the western North Pacific in recent years, contrary to the results of Webster et al [2005].This falling trend was also noted by Kamahori et al [2006] in their recent study on the variability in intense cyclone days in the WNP using RSMC-Tokyo's best track data.…”
Section: Pages 537-538mentioning
confidence: 68%
“…The result is the same if the analysis is extended to include 2005.This downward trend is statistically significant at the 5% level (all significant tests are based on t tests).The trend signifies a falling tendency in typhoon intensity in the western North Pacific in recent years, contrary to the results of Webster et al [2005].This falling trend was also noted by Kamahori et al [2006] in their recent study on the variability in intense cyclone days in the WNP using RSMC-Tokyo's best track data.…”
Section: Pages 537-538mentioning
confidence: 68%
“…The data set provides the central position, central pressure, estimated 10 minute-averaged maximum sustained wind speed, and size (e.g., the radius of 30 knots and 50 knots). They are estimated from observations, namely, aircraft, satellite, surface, and upper air observations (Kamahori et al 2006). In this study, the central position, the central pressure, the maximum 10 minutes-averaged sustained wind speed, and the radii of 30-knot and 50-knot winds in the data set are used as an observation.…”
Section: Best-track Datamentioning
confidence: 99%
“…Kamahori et al (2006) found that the different trends of intense-TC days in JMA and JTWC datasets were due to different intensity categories within different datasets. Kwon et al (2006) also found that the annual TC numbers were different, as were the top 10% of the records, in JMA and JTWC datasets.…”
Section: Introductionmentioning
confidence: 94%
“…of their potential negative impact on numerical weather forecasts, and the uncertainties in the TC best track The biases in the location and intensity of tropical datasets may also confuse the natural trends in TC accyclones (TCs) have received a lot of attention because tivity with spurious variabilities (Kamahori et al 2006;Landsea et al 2006;Wang et al 2008;Wu et al 2006). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation